(untitled) (Research, Society and Development, 2021)
Oral squamous papilloma is a benign neoplasm of epithelial origin, quite common, associated with infection by the Human Papilloma Virus (HPV). Clinically, it presents as an exophytic nodule, soft, painless and generally pedunculated, with a verrucous / papillomatous aspect. This study aims to report a case of a patient with a clinical and histopathological diagnosis of large oral squamous papilloma, with foci of moderate epithelial dysplasia, located in the cheek mucosa and inner side of the lips on the right side. The treatment initially indicated was surgical excision and, later, surgical excision with plastic reconstruction, but the patient due to social issues, fear and lack of family support, even knowing the risks of malignant transformation of the lesion, refused treatment. Despite the need for treatment, the patient has autonomy to make decisions and the right to refuse treatment is recognized by the Brazilian Civil Code as one of the rights of the personality. Respecting the patient’s autonomy characterizes a humanized health system and constitutes one of the main challenges faced by health professionals.